2004
DOI: 10.1086/379970
|View full text |Cite
|
Sign up to set email alerts
|

Ni Abundance in the Core of the Perseus Cluster: An Answer to the Significance of Resonant Scattering

Abstract: Using an XMM-Newton observation of the Perseus cluster we show that the excess in the flux of the 7-8 keV line complex previously detected by ASCA and BeppoSAX is due to an overabundance of nickel rather than to an anomalously high Fe He /Fe He ratio. This observational fact leads to the main result that resonant scattering, which was assumed to be responsible for the supposed anomalous Fe He /Fe He ratio, is no longer required. The absence of resonant scattering points toward the presence of significant gas m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…Churazov et al (2004) use the Fe-K complex of lines at 6.7 keV to find a lower limit to the turbulence in the Perseus cluster. Independently, using the same data, Gastaldello & Molendi (2004) reached similar conclusions. The spectral resolution of the current instruments at these energies is however low, which limits the accuracy of the measurement.…”
Section: Introductionsupporting
confidence: 61%
“…Churazov et al (2004) use the Fe-K complex of lines at 6.7 keV to find a lower limit to the turbulence in the Perseus cluster. Independently, using the same data, Gastaldello & Molendi (2004) reached similar conclusions. The spectral resolution of the current instruments at these energies is however low, which limits the accuracy of the measurement.…”
Section: Introductionsupporting
confidence: 61%
“…The gas in the cluster may be optically thick to resonantly scattered lines (e.g. Gilfanov, Syunyaev & Churazov 1987); however, Dupke & Arnaud (2001), Churazov et al (2004) and Gastaldello & Molendi (2004) observe no evidence for resonant scattering in this cluster. Another effect is known as ‘Fe‐bias’ (Buote 2000), where one underestimates the abundance of the emitting gas if it consists of more than one phase.…”
Section: Abundance Structurementioning
confidence: 99%
“…For the Perseus cluster, an initial analysis suggested that resonant scattering effects were present (Molendi et al 1998;Akimoto et al 1999), although subsequent studies (Churazov et al 2004;Gastaldello and Molendi 2004) did not support these results (see also Ezawa et al 2001;Dupke and Arnaud 2001;Sanders et al 2004). Several other clusters, including M87, Centaurus and A2199, were searched for resonant scattering effects (e.g, Kaastra et al 1999;Akimoto et al 1999Akimoto et al , 2000Sanders and Fabian 2006;Mathews et al 2001;Sakelliou et al 2002), with mixed results.…”
Section: Introductionmentioning
confidence: 99%